2013
DOI: 10.1093/jpids/pit050
|View full text |Cite
|
Sign up to set email alerts
|

Few Patient, Treatment, and Diagnostic or Microbiological Factors, Except Complications and Intermittent Negative Cerebrospinal Fluid (CSF) Cultures During First CSF Shunt Infection, Are Associated With Reinfection

Abstract: Background. The relationship between first and subsequent cerebrospinal fluid (CSF) shunt infections is poorly understood. By understanding the factors associated with increased risk of reinfection, researchers may provide optimal treatment strategies at the time of first infection. The objective of this study was to describe and compare children with and without CSF shunt reinfection. Methods. A retrospective cohort study was performed among 118 children who underwent initial CSF shunt placement and developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
2
11
0
4
Order By: Relevance
“…It should be noted, however, that treatment for patients in this study was not standardized, with different surgical strategies used for shunt removal and replacement, as well as antimicrobial choices. A second large cohort study of 675 patients followed after first infection noted a mean duration of therapy of 7.5 days in 15% of those who experienced reinfection compared to 9 days of treatment in those who did not experience reinfection (differences not significant) [142]. …”
Section: Evidence Summarymentioning
confidence: 95%
See 1 more Smart Citation
“…It should be noted, however, that treatment for patients in this study was not standardized, with different surgical strategies used for shunt removal and replacement, as well as antimicrobial choices. A second large cohort study of 675 patients followed after first infection noted a mean duration of therapy of 7.5 days in 15% of those who experienced reinfection compared to 9 days of treatment in those who did not experience reinfection (differences not significant) [142]. …”
Section: Evidence Summarymentioning
confidence: 95%
“…In a recent study in children, risk factors identified for reinfection were those with complex shunts (multiple shunts placed or any single shunt with multiple catheters together), an atrial shunt, any complication after the first infection (ie, shunt malfunction, hemorrhage, CSF leak), or intermittent negative cultures defined as positive CSF cultures clearing and then returning over the course of treatment [142]. …”
Section: Evidence Summarymentioning
confidence: 99%
“…Reinfection following a primary shunt infection is a challenge that plagues hydrocephalus treatment, occurring in 26% of pediatric patients [84] . Interestingly, patient factors, treatment, and diagnostic factors matter less than evidence of difficulty clearing the primary shunt infection, with intermittent clearance and reemergence of the pathologic organism on serial CSF cultures during the treatment course serving as a negative prognostic indicator [84].…”
Section: Infectionmentioning
confidence: 99%
“…Interestingly, patient factors, treatment, and diagnostic factors matter less than evidence of difficulty clearing the primary shunt infection, with intermittent clearance and reemergence of the pathologic organism on serial CSF cultures during the treatment course serving as a negative prognostic indicator [84]. New research aims at understanding the role of established inflammatory schemes, including the influx of activated M2 macrophages, neutrophils, and chemokines CXCL1, CCL2, and IL-17 in the presence of bacterial biofilm-infected shunt hardware [85, 86].…”
Section: Infectionmentioning
confidence: 99%
“…Contamination of the ventricular catheter at the scalp tract overlying the drill site is thus a potentially important source of infections. With skin incision in the smallest possible level, subcutaneous tissue and the ventricular catheter parts fewer contact with the flora and primarily to prevent infection may be as many complications [12][13][14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%